Clinical Assessment of Dosha Predominance in Shalya Karma Using an Electronic Device Nadi Tarangini (International Journal of Ayurveda and Pharma Research, 2023)
Shalya Karma i.e., operative procedures for fistula-in-ano, fissure-in-ano, haemorrhoids, appendicitis, cholelithiasis, different hernias etc is nowadays very commonly adopted in which surgeons are highly concerned about the recurrences and complications which highly affects the patient’s quality of life. Ayurveda places a lot of stress on feeling the pulse at the radial artery in order to evaluate the Doshas, but it does not restrict the pulse location to just the radial artery and instead makes it plain that the pulse can be felt from eight different places. The radial artery can be used to learn about the Vata, Pitta, and Kapha doshas. Nadi Pariksha uses completely all the basic subjects described in Ayurveda. All spheres of medical science is not remained untouched from Nadi Pariksha. Cause-effect /Karya-karan or Nidan-vyadhi relationship can be finely diagnosed with Nadi Pariksha. Therefore, treatment becomes very unique and specific. Whether treatment is of body or mind, it becomes very clear with Nadi Pariksha. In Ayurveda, post-operative Tridosha specific Nadi Pariksha can be considered a more rationale plan for better outcomes in overcoming the recurrences and gaining a lead over modern surgical complications after Shalya Karma. Nadi Tarangini is a tool to detect and analyze information about our inner health. Nadi Tarangini, the pioneer of the modern Nadi Pariksha system, is a perfect synthesis of hardware and intelligent software powered by artificial intelligence.